PELAYANAN PERIZINAN TENAGA KERJA ASING PADA DINAS TENAGA KERJA KOTA PEKANBARU - Astuti, Wira; Mashur, Dadang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
City Labor Office Pekanbaru provide its services as a proof for Manpower who work in Pekanbaru City. This is useful to prevent the entry of illegal labor and can work for local labor. Problems in labor licensing service in Pekanbaru can be seen from the length of time available, which can be completed within 5 days to 10-15 days.In accordance with Winarsih (2006), service can reflect through Simplicity, Clarity, Certainty of Time, Accuracy, Security, Responsibility, Completeness of facilities and infrastructure, Ease of access, Discipline, Courtesy and Friendliness and Comfort. Informants in the study are employees and the community used as many as 8 people.Result of research that service of work permit in Labor Office of Labor of Pekanbaru City is good enough, only less maximal in the form of service given to interested public. Of the 6 types of theories put forward include: simplicity, clarity, certainty of time, accuracy, completeness of facilities, accessibility, showing service on labor permits Pekanbaru City that has been quite satisfy the existing requirements on the theory. Factors inhibiting labor licensing service in Pekanbaru city can be seen from the internal and external environment. Internal environment is a factor that is less than external factors ie companies that provide less data and information appropriate to work. It is expected that the City Manpower Office Pekanbaru more guidance implementation and technical guidance so that the parties easier to understand it.Keywords : Services, Licensing, Foreign Workers